International Survey on the Use of Arginine Vasopressin in the Postoperative Management of Single Ventricle Patients - Raghavan, Vidya R.; da Cruz, Eduardo M.; Kaufman, Jon; Osorio Lujan, Suzanne (Frontiers in Pediatrics, 2021)
Management of patients with single ventricle physiology after surgical palliation is challenging. Arginine vasopressin has gained popularity in recent years as a non-catecholamine vasoactive medication due to its unique properties. However, data regarding its use in the pediatric population is limited. Therefore, we designed a survey to explore whether and how clinicians use this medication in intensive care units for the postoperative management of single ventricle patients. This international survey aimed to assess usage, practices, and concepts related to arginine vasopressin in pediatric intensive care units worldwide. Directors of pediatric intensive care units who are members of the following international professional societies: European Society of Pediatric Neonatal Intensive Care, Association for European Pediatric and Congenital Cardiology, and Pediatric Cardiac Intensive Care Society were invited to participate in this survey. Of the sixty-two intensive care unit directors who responded, nearly half use arginine vasopressin in the postoperative management of neonatal single ventricle patients, and 90% also use the drug in subsequent surgical palliation. The primary indications are vasoplegia, hemodynamic instability, and refractory shock, although it is still considered a second-line medication. Conceptual benefits include improved hemodynamics and end-organ perfusion and decreased incidence of low cardiac output syndrome. Those practitioners who do not use arginine vasopressin cite lack of availability, fear of potential adverse effects, unclear indication for use, and lack of evidence suggesting improved outcomes. Both users and non-users described increased myocardial afterload and extreme vasoconstriction as potential disadvantages of the medication. Despite the lack of conclusive data demonstrating enhanced clinical outcomes, our study found arginine vasopressin is used widely in the care of infants and children with single ventricle physiology after the first stage and subsequent palliative surgeries. While many intensive care units use this medication, few had protocols, offering an area for further growth and development.